Alpha-carboxynucleoside phosphonates: direct-acting inhibitors of viral DNA polymerases. (16th January 2019) - Balzarini, Jan; Ford, Alan; Maguire, Nuala M; John, Jubi; Das, Kalyan; Arnold, Eddy; Dehaen, Wim; Maguire, Anita
Acyclic nucleoside phosphonates represent a well-defined class of clinically used nucleoside analogs. All acyclic nucleoside phosphonates need intracellular phosphorylation before they can bind viral DNA polymerases. Recently, a novel class of alpha-carboxynucleoside phosphonates have been designed to mimic the natural 2′-deoxynucleotide 5′-triphosphate substrates of DNA polymerases. They contain a carboxyl group in the phosphonate moiety linked to the nucleobase through a cyclic or acyclic bridge. Alpha-carboxynucleoside phosphonates act as viral DNA polymerase inhibitors without any prior requirement of metabolic conversion. Selective inhibitory activity against retroviral reverse transcriptase and herpesvirus DNA polymerases have been demonstrated. These compounds have a unique mechanism of inhibition of viral DNA polymerases, and provide possibilities for further modifications to optimize and fine tune their antiviral DNA polymerase spectrum. Graphical abstract: